2022
DOI: 10.3390/ma15207078
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior of PEEK/PTFE Composites Reinforced with Carbon Fibers and Graphite

Abstract: In this study, poly (ether ether ketone) (PEEK)/polytetrafluoroethylene (PTFE) composites reinforced with carbon fibers (CFs) and graphite (Gr) were fabricated by compressive molding technology. The friction and wear properties of the PEEK/PTFE composites sliding against Si3N4 balls were investigated using ball-on-disk configuration under dry sliding conditions, and the morphologies of the worn surfaces were also observed with a scanning electron microscope (SEM) and a three-dimensional morphometer. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…It has been found that graphene has a coordinated effect with CF in enhancing the wear resistance and tensile strength properties of PEEK, and that PEEK modified with a 20% CF and 10% graphene blend has the best mechanical properties. 59 However, excellent mechanical properties are not enough for bone repair materials, and the low bioactivity still limits their clinical application. Yamane et al 60 used concentrated sulfuric acid and oxygen plasma to act on PEEK with 50% CF content and found that the addition of CF did not affect the generation of surface voids and the introduction of sulfonic and carboxyl groups.…”
Section: Bioactive Materials Modified Peekmentioning
confidence: 99%
“…It has been found that graphene has a coordinated effect with CF in enhancing the wear resistance and tensile strength properties of PEEK, and that PEEK modified with a 20% CF and 10% graphene blend has the best mechanical properties. 59 However, excellent mechanical properties are not enough for bone repair materials, and the low bioactivity still limits their clinical application. Yamane et al 60 used concentrated sulfuric acid and oxygen plasma to act on PEEK with 50% CF content and found that the addition of CF did not affect the generation of surface voids and the introduction of sulfonic and carboxyl groups.…”
Section: Bioactive Materials Modified Peekmentioning
confidence: 99%
“…The lubricant fillers include the familiar PTFE, graphite, MoS 2 , etc (Lu and Friedrich, 1995;Qiao et al, 2007;Khare et al, 2015;Zalaznik et al, 2016;Chen et al, 2020;Li et al, 2022b). Gu et al found that the wear surface of polymethyl methacrylate (PMMA) was uneven with many torn flakes and surface bumps, and the COF curve fluctuated in a wide range, while the wear surface of PTFE/PMMA composites filled with PTFE was relatively smooth with only slight scratches and a smoother COF curve, indicating that the friction process of PMMAbased composites is more stable by filling with PTFE.…”
Section: Friction and Wear Behavior And Improvement Mechanism Of The ...mentioning
confidence: 99%
“…[71] It has been reported that the effect of MPC polymer on preventing bacterial adhesion and biofilm formation is critical. [72][73][74] In Hu's work, PEEK coated with antimicrobial peptide of GL13K demonstrated antibacterial activities against Staphylococcus aureus (S. aureus) bacteria by inducing antibacterial and biofilm-inhibitory effects (Figure 6). [75]…”
Section: Radiation Graftingmentioning
confidence: 99%